Targeting IL‐6 to prevent cardiac allograft rejection. (1st December 2022) - Miller, Cynthia L.; Madsen, Joren C.
Abstract : Outcomes following heart transplantation remain suboptimal with acute and chronic rejection being major contributors to poor long‐term survival. IL‐6 is increasingly recognized as a critical pro‐inflammatory cytokine involved in allograft injury and has been shown to play a key role in regulating the inflammatory and alloimmune responses following heart transplantation. Therapies that inhibit IL‐6 signaling have emerged as promising strategies to prevent allograft rejection. Here, we review experimental and pre‐clinical evidence that supports the potential use of IL‐6 signaling blockade to improve outcomes in heart transplant recipients.